Recurrent Dissemination of SARS-CoV-2 Through the Uruguayan–Brazilian Border - Mir, Daiana; Rego, Natalia; Resende, Paola Cristina; Tort, Fernando; Fernández-Calero, Tamara; Noya, Verónica; Brandes, Mariana; Possi, Tania; Arleo, Mailen; Reyes, Natalia; Victoria, Matías; Lizasoain, Andres; et al. (Frontiers in Microbiology, 2021)
Uruguay is one of the few countries in the Americas that successfully contained the COVID-19 epidemic during the first half of 2020. Nevertheless, the intensive human mobility across the dry border with Brazil is a major challenge for public health authorities. We aimed to investigate the origin of SARS-CoV-2 strains detected in Uruguayan localities bordering Brazil as well as to measure the viral flux across this ~1,100 km uninterrupted dry frontier. Using complete SARS-CoV-2 genomes from the Uruguayan-Brazilian bordering region and phylogeographic analyses, we inferred the virus dissemination frequency between Brazil and Uruguay and characterized local outbreak dynamics during the first months (May-July) of the pandemic. Phylogenetic analyses revealed multiple introductions of SARS-CoV-2 Brazilian lineages B.1.1.28 and B.1.1.33 into Uruguayan localities at the bordering region. The most probable sources of viral strains introduced to Uruguay were the Southeast Brazilian region and the state of Rio Grande do Sul. Some of the viral strains introduced in Uruguayan border localities between early May and mid-July were able to locally spread and originated the first outbreaks detected outside the metropolitan region. The viral lineages responsible for Uruguayan urban outbreaks were defined by a set of between four and 11 mutations (synonymous and non-synonymous) respect to the ancestral B.1.1.28 and B.1.1.33 viruses that arose in Brazil, supporting the notion of a rapid genetic differentiation between SARS-CoV-2 subpopulations spreading in South America. Although Uruguayan borders have remained essentially closed to non-Uruguayan citizens, the inevitable flow of people across the dry border with Brazil allowed the repeated entry of the virus into Uruguay and the subsequent emergence of local outbreaks in Uruguayan border localities. Implementation of coordinated bi-national surveillance systems are crucial to achieve an efficient control of the SARS-CoV-2 spread across this kind of highly permeable borderland regions around the world.